Pengaruh Standar Akuntansi Pemerintahan dan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Dengan Pemoderasi Pengendalian Internal - Gebby Berlian Laoli; Aloysius Harry Mukti (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
This study aims to determine the effect of The Implementation of Government Accounting Standards and The Utilization of Information Technology on the Quality Of Financial Reports with an Internal Control System as a moderating variable BPKAD (Badan Pengelolaan Keuangan dan Aset Daerah) in Bekasi City. This research is quantitative research. With a causal research approach. Primary data collection was carried out by distributing questionnaires to all employees at the BPKAD in Bekasi City. Data analysis was performed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) model through SmartPLS 3.0 software. The results of the study show that (1) The Implementation of Government Accounting Standards has a positive effect on the Quality Performance of Financial Statements; (2) Utilization of Information Technology has a positive effect on the Quality of Financial Reports; (3) Internal Control System as a moderating variable does not have an influence on the relationship between the Implementation of Government Accounting Standards and the Quality of Financial Reports; (4) Internal Control System as a moderating variable has no influence on the relationship between Information Technology Utilization and Financial Report Quality Keywords: Implementation of Government Accounting Standards, Utilization of Information Technology, Quality of Financial Reports, Internal Control System..